The Relationship Between Personality and Academic Performance Between Students - Wahyuni, Sri; Maulana, Hendri; Aulia, Vanya; Neng Ayu Sri wahyuni (INOVATOR, 2024)
This study examines the relationship between personality and students' academic performance. Using quantitative research methods, data was collected from 81 students spread across various study programs. Regression analysis was used to determine the extent to which personality factors such as emotional stability, extroversion, openness, orderliness, and concern for others contribute to academic performance. The regression analysis showed that personality significantly affects academic performance, and a conducive academic environment strengthens this relationship. These findings provide important implications for developing more effective educational strategies to improve students' academic performance through a deeper understanding of the role of personality and academic environment.